Preliminary results from multitemporal infrared thermography surveys at the Wied-Il-Mielah Arch (Island of Gozo) - Grechi, Guglielmo; Martino, Salvatore (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="[null,2,"The Mediterranean region is climatically characterized by considerable daily and seasonal temperature fluctuations due to both direct solar radiation and local weather conditions. The long-term mechanical behavior of jointed rock masses can be actively influenced by the superposition of continuous thermal excursions, especially if exceeding the tens of degrees, and thus rock mass systems could be slowly led toward prone-to-failure conditions. With a view to evaluating the entity of thermal forcings acting on a jointed rock arch, consequently characterizing its thermal behavior, two daily InfraRed Thermography (IRT) monitoring surveys were performed in different seasons (Autumn and Winter) at the Wied-Il-Mielah case study (Island of Gozo in the Maltese archipelago). The obtained preliminary results highlight that the rock mass thermal attitude is strictly related to both the magnitude of the incoming and outcoming heat flux (resulting from the heat-exchange with atmospheric thermal conditions and direct solar radiation) and to the exposure of rock mass surfaces with respect to the incident solar radiation. IRT proved to be a valid remote surveying technique for the definition of the surficial temperature distribution of rock masses, being able to provide useful information in supporting more traditional approaches for the study of thermomechanical effects on rock masses."]" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The Mediterranean region is climatically characterized by considerable daily and seasonal temperature fluctuations due to both direct solar radiation and local weather conditions. The long-term mechanical behavior of jointed rock masses can be actively influenced by the superposition of continuous thermal excursions, especially if exceeding the tens of degrees, and thus rock mass systems could be slowly led toward prone-to-failure conditions. With a view to evaluating the entity of thermal forcings acting on a jointed rock arch, consequently characterizing its thermal behavior, two daily InfraRed Thermography (IRT) monitoring surveys were performed in different seasons (Autumn and Winter) at the Wied-Il-Mielah case study (Island of Gozo in the Maltese archipelago). The obtained preliminary results highlight that the rock mass thermal attitude is strictly related to both the magnitude of the incoming and outcoming heat flux (resulting from the heat-exchange with atmospheric thermal conditions and direct solar radiation) and to the exposure of rock mass surfaces with respect to the incident solar radiation. IRT proved to be a valid remote surveying technique for the definition of the surficial temperature distribution of rock masses, being able to provide useful information in supporting more traditional approaches for the study of thermomechanical effects on rock masses.